Hubungan Kebiasaan Merokok dengan Kejadian Insomnia pada Remaja - Suwanti; Putri Laila Nur Haliza (Universitas Ngudi Waluyo, 2024)
Insomnia is a sleep disorder at night where the individual will feel difficulty of sleeping at night and makes the individual not get enough sleep when he wakes up. One of the factors that cause insomnia is smoking. Some teenagers who have a smoking habit say they have difficulty falling asleep and sleep late at night. The problem of sleep deprivation if left untreated will cause harmful effects, including accidents, physical problems, memory problems, high risk of becoming fat and psychological problems. The purpose of this study was to determine the relationship between smoking habits and the incidence of insomnia in adolescents in Tanjungmojo Village, Kangkung District, Kendal Regency. This research is analytic research with a cross sectional approach. The population is all male adolescent smokers aged 11-20 years in Tanjungmojo Village, Kangkung District, Kendal Regency, totaling 107 people. The sampling technique used is proportional random sampling with a total sample of 84 respondents. Tools for collecting data with smoking habits and KSPBJ-IRS instruments. Data analysis used the Spearman Rank correlation test. The results of this study found that the majority of adolescents in Tanjungmojo Village, Kangkung District, Kendal Regency were light smokers, namely 52 people (61.9%) and those who did not experience insomnia, namely 52 people (61.9%). Based on the results of the Spearman Rank correlation test analysis, the value was (ρ = 0.000 and r = -0.423). There is a relationship between smoking habits and the incidence of insomnia in adolescents in Tanjungmojo Village, Kangkung District, Kendal Regency. Adolescent are advised to reduce the intensity and quantity of smoking so as not to experience insomnia. ABSTRAK Insomnia adalah gangguan tidur pada malam hari dimana individu akan merasakan kesulitan tidur pada malam hari dan membuat individu tidak cukup tidur saat terbangun. Salah satu faktor yang menyebabkan insomnia adalah merokok. Beberapa remaja yang memiliki kebiasaan merokok menyatakan mengalami kesulitan untuk memulai tidurnya dan tidur larut malam. Masalah kurang tidur jika tidak tertangani akan menimbulkan efek yang berbahaya, termasuk kecelakaan, masalah fisik, masalah ingatan, risiko tinggi menjadi gemuk dan masalah psikologis. Tujuan penelitian ini adalah untuk mengetahui hubungan kebiasaan merokok dengan kejadian insomnia pada remaja di Desa Tanjungmojo Kecamatan Kangkung Kabupaten Kendal. Penelitian ini adalah penelitian analitik dengan pendekatan cross sectional. Populasi adalah seluruh remaja laki laki perokok yang berusia 11-20 tahun di Desa Tanjungmojo Kecamatan Kangkung Kabupaten Kendal sebanyak 107 orang. Teknik sampling yang digunakan adalah proportional random sampling dengan jumlah sampel sebanyak 84 responden. Alat untuk mengumpulkan data dengan instrumen kebiasaan merokok dan KSPBJ-IRS (Kelompok Studi Psikiatri Biologik Jakarta- Insomnia Rating Scale). Analisis data menggunakan uji korelasi Spearman Rank. Hasil penelitian ini didapatkan mayoritas remaja di Desa Tanjungmojo Kecamatan Kangkung Kabupaten Kendal merupakan perokok ringan, yaitu sebesar 52 orang (61,9%) dan yang tidak mengalami insomnia yaitu sejumlah 52 orang (61,9%). Berdasarkan hasil analisis uji korelasi Spearman Rank didapatkan nilai (ρ = 0,000 dan r = -0,423). Terdapat hubungan kebiasaan merokok dengan kejadian insomnia pada remaja di Desa Tanjungmojo Kecamatan Kangkung Kabupaten Kendal. Disarankan remaja untuk mengurangi intensitas dan kuantitas merokoknya agar tidak mengalami insomnia.